ANALYSIS OF GOVERNMENT COMMUNICATION STRATEGIES IN CULTURE PRESERVATION IN NORTH SUMATRA - Harianto II; Teguh Satria Amin; Zulfitri Zulfitri (Jurnal Scientia, 2022)
This study aims to find out the communication strategies carried out by the government both at the central and regional levels and related agencies in order to preserve culture, traditions and also the local wisdom in North Sumatra. And this research is to look at the obstacles experienced in implementing communication strategies in order to preserve the unique Malay culture and also the regional culture in North Sumatra . The research subjects are related agencies and also the community who have a role in preserving culture in North Sumatra as well as traditional and cultural institutions and organizations that have this connection . Data collection techniques from this study used observation methods and in-depth interviews with informants or research respondents and used literature or documents that support the research. Data processing used is a qualitative descriptive approach. The results of the descriptive analysis of the research show that the communication strategy used is quite effective or is it just repetition as before both in conveying messages, using methods, and also the role of the media. Then the obstacles that occur and don't run as they should, so that programs in preservation can be hampered and also other things that can make the strategy not run smoothly . Preservation methods such as the Redundancy and Persuasive methods in the form of approaches and establishing cooperative relationships with related parties can facilitate the communication process.